International tourism hub: Function assessment and application. (December 2016) - Meng, Fang; Zou, Tongqian; Li, Hengyun; Ren, Yaqing; Zhang, Pei
This study investigates the functions of international tourism hubs, namely, the gathering and distributing function, transferring function, and management and service function. An assessment index of 49 indicators is developed measuring these functions based on the literature review and a survey of expert panel. Analytical hierarchy process method was applied to determine the importance weight of the indicators. Two cities in China, Beijing and Shanghai, were selected to empirically test the assessment index and compared with the tourism hub functions. The results indicate that Beijing has stronger functions on gathering and distributing tourists, as well as management and services, while Shanghai exceeded on transferring function due to its tourist distribution center. Strategic and managerial implications and suggestions are provided based on the study results.